Movement Patterns of a U-20 National Women’s Soccer Team during Competitive Matches: Influence of Playing Position and Performance in the First Half - Ramos, Guilherme Passos; Nakamura, Fábio Yuzo; Pereira, Lucas Adriano; Junior, Wanderley Brilhante; Mahseredjian, Fábio; Wilke, Carolina Franco; Garcia, Emerson Silami; Coimbra, Cândido Celso (International Journal of Sports Medicine, 2017)
The aim of this study was to determine the match locomotor characteristics of a sample of U-20 Brazilian female soccer players. Seven international matches were analyzed during the 2015 U-20 South American Championship, using global positioning technology. During a typical match, fullbacks and forwards covered greater distances in high-intensity running and sprinting than central defenders and midfielders (effect size [ES]=1.42–3.69). In the final 15 min of a game, total and high-intensity running distance and player load were ≈20 to 35% (ES=0.41–3.86) lower than in the first 15 min period for midfielders, fullbacks, forwards, and central defenders. Sprinting, and high-intensity running distances, and the frequency of accelerations >2 m.s−2 immediately after the most intense 5-min period declined in forwards (ES=1.78–2.67), fullbacks (ES=1.96–5.25), midfielders (ES=1.66–3.77), and central defenders (ES=1.50–4.22). Maintaining ‘high’ levels of activity in the first half resulted in ≈19% reductions in the second half for sprinting distance and frequency of accelerations >2 m.s−2 (ES=0.43 and 0.88), while increases in these locomotor activities were observed in situations with ‘low’ levels of activity (ES=0.64 and 1.12, for sprinting and accelerations >2 m.s−2, respectively) (within-subject analysis). The data demonstrate that high-intensity efforts are reduced during various phases of international matches and overall activity patterns vary among playing positions. This information could be useful in the development and prescription of sex- and age-specific training regimes.
Keywords: time-motion analysis; international tournament; football; match-related fatigue